PERANAN MANAJEMEN RISIKO DALAM TUGAS DAN TANGGUNG JAWAB DIREKSI BANK BERDASARKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Andy Andy; Mahmul Siregar; Suhaidi Suhaidi; Jelly Leviza (USU LAW JOURNAL, 2014)
ABSTRACTBank as a financial intermediary institution often takes a risk of giving negative effect on economy and banking growth. In order to avoid the risk, every management (in this case, board of directors) has to apply risk management in order to give the picture of the loss which be faced by the Bank. Risk is applied by director management in order that the Bank does not undergo loss; therefore, he should keep clients’ finance properly and keep people’s trust. The application of management risk is implicitly stipulated in Law on Banking in due diligence principle and explicitly in PBI No. 11/25/PBI/2009 on Risk Management for Public Bank. If the application of risk management is applied by the director properly and the Bank still undergoes the loss, it is not the director’s responsibility personally. If the loss is caused by the director’s negligence and the lack of carefulness and good faith so that the Bank undergoes the loss, he is personally responsible for it.Keywords: Banking Risk Management, Director’s Responsibility